Dawah in the Digital Age: Utilizing Social Media for the Spread of Islamic Teachings - Jima’ain, Muhammad Talhah Ajmain (UIN Sunan Gunung Djati Bandung, 2023)
In the digital age, the potential of social media as a powerful tool for the dissemination of religious teachings is paramount. Dawah, the process of conveying religious values to align a Muslim's behavior with the principles of Islam, offers a means to promote Islam as a religion of mercy and guidance for all of humanity. Dawah involves several key elements, including the da'i (the one conveying the message), maddah (the content), thariqah (the method), washilah (the medium), and mad'u (the recipient), all working together to achieve the ultimate goal of Dawah: to bring about happiness in this world and the Hereafter. The purpose of Dawah is to foster understanding, awareness, appreciation, and recognition of Islam, as exemplified by the teachings of the Prophet Muhammad (peace be upon him). In the modern era, social media platforms like YouTube, Instagram, Facebook, Twitter, and WhatsApp have emerged as powerful tools for spreading the message of Islam without constraints of time and space, providing an excellent opportunity to reach a diverse global audience and promote Islamic teachings effectively. This study employed qualitative research methods, including content analysis, to assess the effectiveness and reach of Dawah efforts through social media, shedding light on the significant role of these platforms in contemporary religious communication.